Establishing priorities for future land conservation to maximise biodiversity conservation and other ecosystem services in the Tilarán Mountains of Costa Rica - Lindsay Stallcup; Matthew D. Moran; Doris Rojas; Erich Mata (Nature Conservation)
The Monteverde-Arenal Bioregion (MAB), located in the Tilarán Mountains of north-central Costa Rica, contains some of the most biodiverse habitats in Costa Rica and also provides the backbone for some of Costa Rica’s most important ecotourism destinations. Several national parks and private preserves protect a large area of habitat in the region, but this complex of protected areas is isolated from other large protected areas because of deforestation associated mostly with agricultural development, plus a smaller amount of urban development. Furthermore, we are aware of no detailed analysis to identify landscapes in need of protection in order to secure the conservation of the region’s biodiversity into the future. Using GIS technology, we analysed select conservation-related ecosystem services in order to identify the lands of highest future conservation priority outside of existing protected areas in the MAB. We identified large areas of habitat on the Pacific slope to the south and west of the existing protected areas and habitat adjacent to Lake Arenal to the northwest of existing protected areas as having the highest ecosystem services values. In contrast, most lands on the Caribbean slope outside of the existing protected areas had comparatively lower ecosystem services values. Based on this analysis, we recommend that future conservation efforts, including potential land purchase, should focus on conserving mid-elevation Pacific slope forests and land along previously proposed biological sub-corridors that could connect the MAB to other existing protected areas. Our analysis shows that many important landscapes for biodiversity conservation in and near the MAB currently exist outside of protected areas, making many species found in those areas vulnerable to human activities. The opportunity to connect currently protected areas to one another through effective biological corridors still remains, possibly through conservation partnerships with landowners or direct land purchase, but time could be short as increasing development and changing land-use patterns threaten to further isolate habitats in the MAB.